Critical Analyses of John Burton’s Theories on the Process of the Compilation of the Holy Qur’ān - Dr. Muhammad Khubaib; Sajid U Rahman (jihat-ul-islam, 2022)
The Holy Qur’ān has been revealed to the last Prophet Muhammad (P.B.U.H) by Almighty Allah. So it is the Word of Almighty Allāh which He has promised to guard by Himself. John Burton is an Orientalist. He has written a book regarding the Holy Qur’ān named “The Collection of the Qur’ān”. Like other Orientalists he has tried to create doubts in the minds of people regarding the process of the compilation of the Qur’ān. In the second part of his book Burton has mentioned strange theories about the collection of the Qur’ān. In this article, Burton’s theories on the process of the compilation of the Qur’ān have been reviewed and it has been proved that the Holy Prophet himself got the whole Qur’ān written in his lifetime. Measures adopted for the preservation of the Qur’ān in the Prophet’s lifetime like “memorizing” and “writing,” have been explained with detail. The contribution of Hazrat Abu Bakr and Hazrat Uthmān in the process of the compilation of the Qur’ān has been mentioned that Hazrat Abu Bakr got the written sheets of the Holy Qur’ān compiled in one book and Hazrat Uthmān is credited to gather the whole Ummah on one agreed upon official mus’haf consisting of seven letters on which the Holy Qur’an has been revealed.